Toward a Refined Definition of Monocyte Subsets - Ziegler-Heitbrock, Loems; Hofer, Thomas P. (Frontiers in Immunology, 2013)
In a nomenclature proposal published in 2010 monocytes were subdivided into classical and nonclassical cells and in addition an intermediate monocyte subset was proposed. Over the last couple of years many studies have analyzed these intermediate cells, their characteristics have been described and their expansion has been documented in many clinical settings. While these cells appear to be in transition from classical to nonclassical monocytes and hence may not form a distinct cell population in a strict sense, their separate analysis and enumeration is warranted in health and disease.